2018
DOI: 10.1136/injuryprev-2017-042649
|View full text |Cite
|
Sign up to set email alerts
|

New York City’s window guard policy: four decades of success

Abstract: This article describes each stage of policy development, starting with epidemiological studies defining the scope of the problem in the 1960s and pilot-testing of the window guard intervention. We describe the adoption, implementation and enforcement of the rule. In addition, we show how the rule was modified over time and document the rule's impact on window fall incidence in NYC. We describe litigation that challenged the rule's constitutionality and discuss the legal arguments used by opponents of the rule.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Falls from heights and buildings more broadly are the leading cause for major traumas in children, but the specific focus of this review was on neurosurgical injuries caused by falls from windows as this has been identified as the most frequent fall-related incident by several studies across the globe [ 9 , 15 , 16 ]. This high frequency of occurrence has led to the establishment of several successful campaigns and programs over the years that aimed mainly at raising awareness regarding relevant risks and dangers, and revising safety policies for windows of residential and commercial buildings [ 17 ]. “Children can’t fly” and “Kids can’t fly” were two of the most successful of such programmes, managing to reduce incidents of falls from windows by 96% for children under the age of five, within their first 10 years of implementation in New York and Boston respectively [ 3 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Falls from heights and buildings more broadly are the leading cause for major traumas in children, but the specific focus of this review was on neurosurgical injuries caused by falls from windows as this has been identified as the most frequent fall-related incident by several studies across the globe [ 9 , 15 , 16 ]. This high frequency of occurrence has led to the establishment of several successful campaigns and programs over the years that aimed mainly at raising awareness regarding relevant risks and dangers, and revising safety policies for windows of residential and commercial buildings [ 17 ]. “Children can’t fly” and “Kids can’t fly” were two of the most successful of such programmes, managing to reduce incidents of falls from windows by 96% for children under the age of five, within their first 10 years of implementation in New York and Boston respectively [ 3 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Head injuries are the most common injury sustained in these falls 7 , which we also found to be true in our cohorts. These injuries and fatalities are preventable, and window guards have been adopted as part of the Health Code in cities such as New York with significant decrease in annual fatal and non-fatal falls from windows 8 , 9 . However, the efficacy of interventions aimed at reducing pediatric falls from windows have been poorly studied and variable results have been reported 10 .…”
Section: Discussionmentioning
confidence: 99%
“…These key features reflect the ways in which communities are strengthening systems to drive population-level impact on injury and related health outcomes, rather than striving for fidelity to specific evidence-based programmes. Leonardo et al 11 describe a quality improvement model for building state public health capacity to test, implement and spread change ideas for reducing childhood injury and death, and Toprani et al 12 explain how a pilot injury prevention programme grew to absorb other system impacts (eg, building codes, home inspections, policy change, surveillance and civil liability) and resulted in significant injury reduction.…”
mentioning
confidence: 99%